Carne de Raia (Gymnura altavela) liofilizada: obtenção, caracterização e aplicação em biscoito tipo salgado - Costa, Janaina de Paula (2020)
The increased needing for convenience products, easily prepared, motivated by the new lifestyle and the domination of shelves by products of high quality and diversification, has changed the traditional food consumer. This way, correct processing to guarantee the conservation of highly perishable foods, such as fish, and the use of new technological transformations are of importance, increasing its shelf life, convenience for the consumer and value added. This work aims to develop a new way of making meat available and with a longer commercial life, without the needing of another conservation process such as refrigeration or freezing, and this product can be used as raw material for biscuit, bread, soups, sauces, moqueca (Brazilian dish), instant noodles or in the preparation of elaborated dishes. Initially, the influence of the process conditions (freezing time and freeze-drying time) on the water activity, moisture and yield of the product were evaluated through two experimental designs. Then the product stability study was carried out by monitoring physical-chemical parameters (aw, moisture, pH, N_BVT, TBARS, color), microbiological and changes in volatile compounds, for 180 days, and the influence of type of packaging in the preservation of the product, as well as the hygroscopic behavior of lyophilized ray meat. In the last stage, the product was applied in the formulation of salty biscuit and its sensory evaluation. The results of the two plans indicated that that 2h of freezing and 16h of drying are sufficient to dehydrate the ray meat, with a reduction of 96.85% of the moisture and a water activity of less than 0.6, limit for the development of microorganisms. The results of the stability study showed that lyophilized ray meat undergoes little change over the storage period and if it is packed in laminated packaging, the conservation is greater. The profile of volatile compounds changes with 29 new compounds after 180 days of storage. The GAB model was the one that best represented the adsorption isotherms. Lyophilized ray meat presents itself as a potential for commercialization with its deterioration process at low speed. The application of 5, 10 and 15% lyophilized ray meat in the biscuit formulation did not affect the physical properties of the biscuits and increased the nutritional value. The incorporation of 5% did not differ sensorially from the control formulation, and among the formulations with added fish, it was preferred.